Association between polymorphisms in the GRIN1 gene 5' regulatory region and schizophrenia in a northern Han Chinese population and haplotype effects on protein expression in vitro - Yong-ping Liu; Mei Ding; Xi-cen Zhang; Yi Liu; Jin-feng Xuan; Jia-xin Xing; Xi Xia; Jun Yao; Bao-jie Wang (BMC, 2019)
Abstract Background Schizophrenia is a severe neurodevelopmental disorder with a complex genetic and environmental etiology. Abnormal glutamate ionotropic N-methyl-D-aspartate receptor (NMDA) type subunit 1 (NR1) may be a potential cause of schizophrenia. Methods We conducted a case-control study to investigate the association between the GRIN1 gene, which encodes the NR1 subunit, and the risk of schizophrenia in a northern Chinese Han population using Sanger DNA sequencing. The dual luciferase reporter assay was used to detect the influence of two different haplotypes on GRIN1 gene expression. Results Seven SNPs (single nucleotide polymorphisms), including rs112421622 (− 2019 T/C), rs138961287 (− 1962--1961insT), rs117783907 (−1945G/T), rs181682830 (−1934G/A), rs7032504 (-1742C/T), rs144123109 (−1140G/A), and rs11146020 (−855G/C) were detected in the study population. Rs117783907 (−1945G/T) was associated with the occurrence of schizophrenia as a protective factor. The genotype frequencies of rs138961287 (− 1962--1961insT) and rs11146020 (−855G/C) were statistically different between cases and controls (p < 0.0083). The other four variations were not shown to be associated with the disease. Two haplotypes were composed of the seven SNPs, and distribution of T-del-G-G-C-G-G was significantly different between the case and control groups. However, the dual luciferase reporter assay showed that neither of the haplotypes affected luciferase expression in HEK-293 and SK-N-SH cell lines. Conclusions The GRIN1 gene may be related to the occurrence of schizophrenia. Additional research will be needed to fully ascertain the role of GRIN1 in the etiology of schizophrenia.